2016
DOI: 10.1038/am.2016.130
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired tuning of glycol chitosan for 3D cell culture

Abstract: Three-dimensional (3D) cell culture systems have promising applications compared with conventional two-dimensional cell culture systems. Herein, we report a facile method for the formation of 3D spheroids using novel thermo-reversible polysaccharide-based hydrogels. A series of thermo-reversible hydrogels consisting of N-acyl glycol chitosans (NAGCs) are synthesized through a simple N-acylation reaction, and the degree of acylation is finely tuned to obtain adequate thermoreversible properties and gel stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Hence, such complexes serve as a platform for tissue engineering and creating favorable environments for cell survival in vitro . Chitosan imparts nonadhesiveness and a temperature‐tunable behavior to the complexes . Combining chitosan and gelatin at optimal ratios followed by crosslinking can tailor properties, such as mechanics, pore size, and cell viability .…”
Section: Gelatin–polysaccharides Composites In Cell Culture and Tissumentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, such complexes serve as a platform for tissue engineering and creating favorable environments for cell survival in vitro . Chitosan imparts nonadhesiveness and a temperature‐tunable behavior to the complexes . Combining chitosan and gelatin at optimal ratios followed by crosslinking can tailor properties, such as mechanics, pore size, and cell viability .…”
Section: Gelatin–polysaccharides Composites In Cell Culture and Tissumentioning
confidence: 99%
“…[149][150][151][152] Chitosan imparts nonadhesiveness and a temperature-tunable behavior to the complexes. 153 Combining chitosan and gelatin at optimal ratios followed by crosslinking can tailor properties, such as mechanics, pore size, and cell viability. 154 Chitosan and gelatin can be chemically conjugated to form hybrid biomaterials.…”
Section: Gelatin-polycationic Chitosanmentioning
confidence: 99%
“…In this live and dead assay, we used epithelial cell aggregates to provide an environment similar to the mucosa, which consists of one or more layers of epithelial cells. Generally, a greater number of dead cells are shown in the central region of aggregates because nutrient and oxygen uptake by cells in the inner core of aggregates may be reduced because of the limitation of diffusion [ 37 , 38 ]. In the case of the SH-HGC, it was observed that reasonable numbers of cells in aggregate were viable.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the application of GC derivatives as drug carriers, recently, novel GC derivatives have still been developed for other biomedical applications. For example, an N -hexanoyl GC derivative as a thermo-reversible hydrogel can be useful as a convenient method for the development of in vitro 3D cell culture systems when used to coat the surfaces of cell culture dishes [ 88 ]. GC-EDTA (ethylenediaminetetraacetic acid) derivative was developed as an efficient metalloenzyme inhibitor to protect peptides and proteins from enzymatic degradation [ 89 ].…”
Section: Discussionmentioning
confidence: 99%